Reimagining Communication Studies in a Digital Age - Lindholm, Vilhelm (My University, 2021)
The COVID-19 pandemic challenged society in many ways. In schools and universities, classrooms and campuses were vacated as teaching moved online. In this massive, forced leap of digitalization, the flexibility of digital solutions was harnessed on a large scale, leading to formal education continuing despite the lockdowns. However, despite technology providing possibilities to teach remotely, the overall organization of courses was still stuck in a bureaucratic system not built on the flexible affordances of the digital age. This master’s thesis presents an alternative way of organizing university studies, through the presentation and testing of the Communication Studies Tracker (CST). The CST is designed to allow students to complete their obligatory communications studies at university without having to attend any specific language or communication courses. Instead, the system would track and process communicative tasks done by students, until a sufficient amount of successful experience is gathered in the required languages and focus areas. To gauge the viability of an approach based on the above concept, a usability test of the CST was organized, in which five students and five teachers tested and discussed the system and its underlying concept. The results show participants felt that the CST would provide increased flexibility and meaningfulness in communication studies. Further, participants felt the concept was viable and suitable for implementing at the University of Turku. The main challenges discovered were related to support for weaker students and coordination of group work. The teacher testers also expressed concern regarding how a course-free system would be implemented by the university administration, especially concerning resource allocation.

Covid-19-pandemia haastoi yhteiskuntamme monin tavoin. Kouluissa ja yliopistoissa luokkahuoneet ja kampukset tyhjenivät, kun opetus siirtyi verkkoon. Tässä massiivisessa pakotetussa digitalisoinnin harppauksessa digitaalisten ratkaisujen joustavuutta hyödynnettiin laajamittaisesti, mikä johti muodollisen koulutuksen jatkumiseen tilojen suluista huolimatta. Vaikka tekniikka pystyy tarjoamaan opetusta etäyhteyden välityksellä, kurssien yleinen rakenne juontaa juurensa byrokraattisesta järjestelmästä, joka ei perustu digitaalisen aikakauden joustaviin mahdollisuuksiin. Tämä tutkielma esittää vaihtoehtoisen tavan järjestää yliopisto-opintoja esittelemällä ja testaamalla Communication Studies Tracker (CST) järjestelmän. CST on suunniteltu antamaan opiskelijoille mahdollisuus suorittaa yliopisto-tutkinnon pakolliset viestintäopinnot käymättä mitään erityisiä kieli- tai viestintäkursseja. Sen sijaan järjestelmä seuraa ja käsittelee opiskelijoiden tekemiä kommunikaatiotehtäviä, kunnes vaadittavilla kielillä ja kohdealueilla on kerätty riittävä määrä hyväksyttyjä kokemuksia. Yllä olevaan konseptiin perustuvan lähestymistavan toimivuuden arvioimiseksi järjestettiin CST:n käytettävyystesti, jossa viisi opiskelijaa ja viisi opettajaa testasivat järjestelmää ja keskustelivat sen taustalla olevasta konseptista. Tulokset osoittavat, että osallistujat kokivat, että CST lisäisi joustavuutta ja mielekkyyttä viestintäopinnoissa. Tämän lisäksi osallistujat kokivat konseptin toteuttamiskelpoiseksi Turun yliopistossa sekä soveltuvan hyvin yliopiston koulutustavoitteisiin. Suurimmat haasteet liittyivät heikompien opiskelijoiden tukemiseen ja ryhmätyön koordinointiin. Opettajatestaajat ilmaisivat myös huolensa siitä, miten yliopiston hallinto toteuttaisi kurssittoman järjestelmän, kantaen erityisen huolen resurssien kohdentamisesta.
Keywords: Digitalization, usability, communication, curriculum design, affordances